PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS IV SD IT AZ-ZAHIRA LUBUKLINGGAU - Putri, Ocha; Fitriyana, Nur; Abadi, Candres (Primary Education Journal Silampari (PEJS), 2024)
This study aims to determine the mathematics learning outcomes of fourth-grade students of SD IT Az-Zahira Lubuklinggau after the Contextual Teaching And Learning learning model is applied. This research method uses Pre-test and Post-test. Sampling was taken from the population, the sampling technique in this study used saturated sampling. The instrument used was in the form of 10 essay questions. The data analysis technique used the z-test at a significance level of a = 0.05. The results of the study obtained that Zcount = 6.44 ≥ Ztable = 1.64, so it can be concluded that Ha is accepted and Ho is rejected the Mathematics learning outcomes of fourth-grade students of SD IT Az-zahira Lubuklinggau after the application of the Contextual Teaching And Learning (CTL) learning model Significantly complete with an average learning outcome of 79.30. Keywords: Learning Outcomes, Mathematics, Contextual Teaching And Learning